Bodily Fluids: Female Corporeality as Neo-Victorian Agency in Graham Swift’s Waterland - Orr, Ashley (Australasian Journal of Victorian Studies, 2016)
A hallmark of neo-Victorian fiction is its preoccupation with recovering and reimagining lost voices from the past. The increased critical attention toward feminist neo-Victorian fiction in the late 1990s and early 2000s fuelled an ongoing debate about the genre’s capacity to redress historical silences toward marginalised groups. The representation of women in neo-Victorian fiction has divided critics: on the one hand, these novels are viewed as key interventions in contemporary gender inequality and, on the other, as opportunistic works designed to capitalise on the fetishisation of the Other. Despite the recurring presence of transgressive female bodies in Graham Swift’s neo-Victorian novel Waterland (1983), criticism of the novel has thus far neglected to engage with its relationship to the feminist movement in the genre. The majority of scholarship on the novel focuses on Tom Crick’s narrative as a prime example of postmodern historiography or historiographic metafiction. As a result, little attention has been paid to the female characters in Waterland, while the scholarship that does exist in this area perpetuates the perception of these women as powerless pawns in the grand narrative of male-authored history. This paper addresses the critical silence toward Waterland’s female characters by employing an interdisciplinary methodology drawn from memory studies, corporeal feminism, and neo-Victorian criticism. I argue that repositioning our attention from memory-as-story to memory-as-body reveals the agency inherent in the actions of Waterland’s women, particularly with regard to Crick’s wife Mary and her Victorian-era counterpart, Sarah Atkinson. Reading the novel through the embodied memories of its female characters demonstrates their capacity to successfully intervene in the patriarchal discourse that seeks to overpower them.